2010
DOI: 10.1007/s11845-010-0570-7
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of resource leveling to optimize ERCP efficiency

Abstract: Resource leveling can be applied to balance procedure provision with demand to cope with fluctuations in demand. The impact of resource leveling can be truly measured only by implementing these changes and prospectively studying the effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Indeed, endoscopic retrograde cholangiopancreatography (ERCP) [63] is commonly used in the clinical setting to study and treat problems of bile and pancreatic ducts. The existence of an established procedure to reach the human pancreas in a minimally-invasive manner opens the possibility of safe gene transfer to the pancreas of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endoscopic retrograde cholangiopancreatography (ERCP) [63] is commonly used in the clinical setting to study and treat problems of bile and pancreatic ducts. The existence of an established procedure to reach the human pancreas in a minimally-invasive manner opens the possibility of safe gene transfer to the pancreas of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the retrograde pancreatic intraductal injection can be performed in large animals and humans through a less invasive, nonsurgical clinical procedure called endoscopic retrograde cholangiopancreatography [39], opening the possibility for a future translation of successful treatments to humans. In addition, this approach provides a shortcut to the generation of relevant animal models of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Davies et al (122) found that introducing a non-urgent upper GI endoscopy service at the weekend reduced length of inpatient stay without increased mortality. Resource leveling studies on ERCP have also proposed a half-day Saturday list (123).…”
Section: Proposed Ways Of Reducing Time To Cholecystectomymentioning
confidence: 99%